Biology of IDH mutant cholangiocarcinoma - Wu, Meng‐Ju; Shi, Lei; Merritt, Joshua; Zhu, Andrew X.; Bardeesy, Nabeel (Hepatology (Baltimore, Md.), 2022)
Isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) are the most frequently mutated metabolic genes across human cancers. These hotspot gain‐of‐function mutations cause the IDH enzyme to aberrantly generate high levels of the oncometabolite, R‐2‐hydroxyglutarate, which competitively inhibits enzymes that regulate epigenetics, DNA repair, metabolism, and other processes. Among epithelial malignancies, IDH mutations are particularly common in intrahepatic cholangiocarcinoma (iCCA). Importantly, pharmacological inhibition of mutant IDH (mIDH) 1 delays progression of mIDH1 iCCA, indicating a role for this oncogene in tumor maintenance. However, not all patients receive clinical benefit, and those who do typically show stable disease rather than significant tumor regressions. The elucidation of the oncogenic functions of mIDH is needed to inform strategies that can more effectively harness mIDH as a therapeutic target. This review will discuss the biology of mIDH iCCA, including roles of mIDH in blocking cell differentiation programs and suppressing antitumor immunity, and the potential relevance of these effects to mIDH1‐targeted therapy. We also cover opportunities for synthetic lethal therapeutic interactions that harness the altered cell state provoked by mIDH1 rather than inhibiting the mutant enzyme. Finally, we highlight key outstanding questions in the biology of this fascinating and incompletely understood oncogene.